Solids level measurement and detection handbook - Lewis, Joe (The Momentum Press digital library, 2012)
Inside, you will find the subject of level measurement and detection of powder and granular bulk solids is covered in an easy-to-understand manner, allowing you to choose to study, skim, or just reference any chapter as needed. With this detailed text, you'll find it much easier to find just what you need in a timely fashion versus thumbing through, page-by-page. Each chapter deals with a specific subject and includes chapter summary, objectives, the text body, and even study questions and answers.